Implementing service level objectives (O'Reilly Media, Inc., 2021)
Service-level objectives (SLOs)—the bedrock upon which the discipline of site reliability engineering (SRE) was built—have never been more popular. But it can be difficult to find practical advice that helps you actually get started. And while the concepts are easy to learn, it turns out that actually putting them into practice takes much more work than most people realize. Expert Alex Hidalgo introduces you to an SLO-based approach to reliability and walks you through real-world example applications—showing you how to get started on your SLO journey right away. Learn how to do SLOs the right way to get the data you need to make better decisions, understand your services better, increase your release cadence, and end up with happier customers.